The Evolutionary Origin of C4 Photosynthesis in the Grass Subtribe Neurachninae . Issue 1 (14th October 2019) - Khoshravesh, Roxana; Stata, Matt; Busch, Florian A.; Saladié, Montserrat; Castelli, Joanne M.; Dakin, Nicole; Hattersley, Paul W.; Macfarlane, Terry D.; Sage, Rowan F.; Ludwig, Martha; Sage, Tammy L.
Abstract : In multiple Neurachne species, organelles and glycine decarboxylase show varying enhancement in the mestome sheath, suggesting that C2 photosynthesis gradually evolved from ancestral C3 plants. Abstract: The Australian grass subtribe Neurachninae contains closely related species that use C3, C4, and C2 photosynthesis. To gain insight into the evolution of C4 photosynthesis in grasses, we examined leaf gas exchange, anatomy and ultrastructure, and tissue localization of Gly decarboxylase subunit P (GLDP) in nine Neurachninae species. We identified previously unrecognized variation in leaf structure and physiology within Neurachne that represents varying degrees of C3 –C4 intermediacy in the Neurachninae. These include inverse correlations between the apparent photosynthetic carbon dioxide (CO2 ) compensation point in the absence of day respiration ( C * ) and chloroplast and mitochondrial investment in the mestome sheath (MS), where CO2 is concentrated in C2 and C4   Neurachne species; width of the MS cells; frequency of plasmodesmata in the MS cell walls adjoining the parenchymatous bundle sheath; and the proportion of leaf GLDP invested in the MS tissue. Less than 12% of the leaf GLDP was allocated to the MS of completely C3 Neurachninae species with C * values of 56–61 μmol mol −1, whereas two-thirds of leaf GLDP was in the MS of Neurachne lanigera, which exhibits a newly-identified, partial C2 phenotype with C * of 44 μmol mol −1 . Increased investment of GLDP in MS tissue of the C2 species was attributed to more MS mitochondria and less GLDP in mesophyll mitochondria. These results are consistent with a model where C4 evolution in Neurachninae initially occurred via an increase in organelle and GLDP content in MS cells, which generated a sink for photorespired CO2 in MS tissues.